A model for new product introduction under resource constraints and product interdependence. (2016) - Dash, Binay; Narendran, T.T.; Gajanand, M.S.
Firms face the challenge of timing product entry decisions. Usually, firms will have a set of product ideas on the bench and a constrained amount of product development resources. Product development happens in multiple stages. Deciding on which products should be processed through the product development stages in a resource constrained environment to help the firm achieve maximum revenue/profit is a challenging problem. The complexity gets further increased if products are inter-related/sequential in terms of resource needs with respect to attributes. This paper presents a mixed integer linear programme (MILP) model which can help an organisation to select on products it wants to launch and feasible launch timings considering multi-stage product development cycle in a resource constrained environment. This paper further proposes an enhancement to the MILP and a branch-n-bound (B&B) algorithm which will help the firm figure out optimum strategies if products are inter-related.